The implementation of kangaroo mother care and nurses' perspective of barriers in Iranian' NICUs - Mahboobeh Namnabati; Sedigheh Talakoub; Majid Mohammadizadeh; Fatemesadat Mousaviasl (Wolters Kluwer Medknow Publications, 2016)
Background: Kangaroo mother care (KMC) is the most implementation intervention in caring of the infants, as in this method, both the mothers and infants are cared. The World Health Organization recommends implementation of KMC for all infants. However, there are some barriers in the way of its application. The purpose of this study was evaluation of the practical application of KMC and nurses' perspective about its implantation barriers in the neonatal intensive care units (NICUs) in Iran. Materials and Methods: The descriptive study was conducted on 96 infants and 80 nurses working in the NICUs of two university hospitals in Isfahan, Iran. Data were collected by a two-section questionnaire and analyzed by t-test through SPSS 14. Results: Study findings indicated that mean weight and age of the infants with KMC were 1510 g and 32 weeks, respectively. KMC was implantation for 32 min in a day. From nurses' perspective, mother-related barriers were the main barriers in the implantation of KMC as mothers were not present by their infants. Another barrier was the mothers' fear of touching their infants. In the domain of organizational barriers, physician's order was found to be the most important barrier in application of KMC. Conclusions: Identifying barriers in implantation of KMC is essential to support the mothers. Regarding mother-related barriers, organizational barriers, and the need for a physician's order for implementation of KMC, policy makers must provide facilities and equipment for applying KMC practice for mothers and improve the protocol of KMC in the NICU.